Quality related substrates and enzyme in tea as influenced by weather parameters - Shalini, D.; Kumar, R. Raj (Journal of Plantation Crops, 2011)
Recent threat on global warming and change in climate are not only the topic related with agricultural and biomass productivity; but on the basis of quality consciousness consumers demand, agriculturalists are indebted to offer due importance to the quality of the agricultural commodities. Quality attributes depends mainly upon the biochemical constituents. How far climatic changes influence the quality attributes of tea are unknown. In the pilot scale study, polyphenols, catechins and their oxidative enzyme are considered and variations in their ratios with respect to prevailing climatic conditions of the Anamallais are attempted. Crop shoots were collected at monthly intervals and subjected to determination of polyphenols, catechins and polyphenol oxidase assay. Weather data collected at UPASI meteorological observatory were used for correlation and factor analysis. Irrespective of the clones, "Cambod" cultivars registered higher quantum of polyphenols followed by "Assam" cultivar. Clones studied within the taxonomic group also significantly varied among them, irrespective of the sampling time. As the catechins are polyphenol derivates, the same trend was observed with total catechin content. Among the clones, SA-6 registered least amount of polyphenols and catechins when compared to other clones. Ratio of catechin to polyphenol exhibited different trend; "Cambod" cultivars registered higher values in catechin, polyphenol ratio followed by "China" and "Assam" cultivars. Polyphenol oxidase activity was significantly varied among the jats and the clones within the taxa. Microclimatic variables played an important role in accumulation of predominant quality constituents, polyphenols or catechins and the enzyme, poly phenol oxidase. Sunshine hours positively related with the above said biochemicals while rainfall has negative influence on the biochemical constituents. Maximum temperature had positive and significant correlation with quality constituents whereas, minimum temperature registered negative impact on their production. Relative humidity recorded at 8.00 am and 2.30 pm exerted negative influence on polyphenols, catechins and PPO activity. Multiple regression models derived based on the climatic variables are presented and discussed in detail.